2023
DOI: 10.1002/ar.25207
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type and metabolic characteristics of skeletal muscle in 16 breeds of domestic dogs

Abstract: The domestic dog (Canis lupus familiaris) species comprises hundreds of breeds, each differing in physical characteristics, behavior, strength, and running capability. Very little is known about the skeletal muscle composition and metabolism between the different breeds, which may explain disease susceptibility. Muscle samples from the triceps brachii (TB) and vastus lateralis (VL) were collected post mortem from 35 adult dogs, encompassing 16 breeds of varying ages and sex. Samples were analyzed for fiber typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Also, in a study performed in ducks by Li and co-workers, no significant differences were found in the fCSA between the breeds examined (Li et al, 2016). Similarly, in a study by van Boom et al (2023), the fCSA in two different muscles of 16 dog breeds showed no significant differences. Overall, this suggests that the fCSA is not discriminative between breeds of the same species and that species mainly differ in the fCSA of non type I fibers.…”
Section: The Added Value Of Comparing Different Archetypical Breeds A...mentioning
confidence: 86%
See 1 more Smart Citation
“…Also, in a study performed in ducks by Li and co-workers, no significant differences were found in the fCSA between the breeds examined (Li et al, 2016). Similarly, in a study by van Boom et al (2023), the fCSA in two different muscles of 16 dog breeds showed no significant differences. Overall, this suggests that the fCSA is not discriminative between breeds of the same species and that species mainly differ in the fCSA of non type I fibers.…”
Section: The Added Value Of Comparing Different Archetypical Breeds A...mentioning
confidence: 86%
“…For instance, at baseline, Andalusian horses, which are well known for powerful equestrian activities of rather short duration, such as dressage, show jumping and driving, have a significantly larger fCSA across all muscle fiber types when compared to Dutch Warmblood horses, Arabian and Thoroughbred horses ( Rivero and Diz, 1992 ; Serrano and Rivero, 2000 ; Rietbroek et al, 2007 ). Similarly, the Greyhound, which is the canine archetype of acceleration power, has a larger mfCSA when compared to a Yorkshire Terrier ( van Boom et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%